Light-sensing behaviors of organic/n-Si bio-hybrid photodiodes based on malachite green (MG) organic dye - Yılmaz, Mehmet; Koçyiğit, Adem; Aydoğan, Şakir; İncekara, Ümit; Turşucu, Ahmet (SPRINGER, 2020)
We fabricated malachite green (MG) dye-based photodiode between Co metal and n-Si by spin coating technique. The electrical and photoresponse properties of the MG/n-Si photodiode were studied via current-voltage characteristics as a function of the light power intensity in the range of 100 and 400 mW/cm(2). Furthermore, capacitance-voltage measurements were performed on the MG/n-Si photodiode for various frequencies. The photodiode exhibited a good rectification behavior in dark as well as various light illumination intensities with a good photodiode characteristics since generated photocurrent of the MG/n-Si photodiode increased depending on the exposed light intensity. The leakage current was obtained as 2.96 x 10(-5) A under dark and increased to 3.83 x 10(-5) and 11.5 x 10(-5) A for 100 and 400 mW/cm(2) light intensities, respectively. This clear increase at the leakage current with light illumination can be attributed to the generation of electron-hole pairs in MG organic dye as well as semiconductor and forming an internal electrical field in the interface of the photodiode. Furthermore, main photodiode parameters such as ideality factor and barrier height were calculated by thermionic emission theory and Norde method. Both these parameters and responsivity of the photodiode to the light illumination were obtained as function of the light illumination intensity. The capacitance-voltage measurements revealed that the photodiode exhibited capacitance behavior 100 and 1000 kHz frequency range. The photodiode showed same built-in potential and barrier height values with changing frequency, but their values were higher than obtained from thermionic emission theory. The light intensity effects on the MG dye-based photodiode highlights that this dye may be a good candidate for optoelectronic applications.